First Language Interferences on Minangkabau-Indonesian EFL Students’ Linguistic Repertoire in the Process of Advancing their Multilingual Awareness - Syayid Sandi Sukandi (Universitas Negeri Padang, 2014)
To be able to communicate smoothly in English needs a lot of courage. This smoothness, of course, is seen as linguistic competence where students can use a language fully into its optimal use in society. In this case, Indonesian EFL students are growing up in social environment where they encounter many ethnic languages as the first language across the archipelago. Therefore, Bahasa Indonesia cannot be seen as the first language. Dealing with this article, the focus of the problem being addressed is the interferences of the first language use toward Minangkabau-Indonesian EFL students’ linguistic repertoire in the process of advancing the multilingual awareness. Minangkabau is an ethnic community that exists in the province of West Sumatra, Indonesia. To learn some of the particular nuances of how this language interfere the process of learning English as a Foreign Language would be one of the issues discussed in this article. The researcher uses data that are taken from daily interactions happening in the classrooms and outside the classrooms as the examples for the first language interferences. Since the researcher is also a growing up individual in Minangkabau society, therefore, recognizing some of the interferences of this language toward the process of learning English is doable. The argument is that to lead EFL students to have a sense of multilingual awareness would be possible by helping them manage their first language interferences in achieving standardized linguistic repertoire under the guidance of us as their English language educator.